2014
DOI: 10.19027/jai.12.14-17
|View full text |Cite
|
Sign up to set email alerts
|

Dietary vitamin E on the reproductive performance of the fantail goldfish Carassius auratus auratus

Abstract: This research was conducted to examine the different dose of vitamin E in the diet on female broodstock reproduction performance of the fantail goldfish Carassius auratus auratus. This research consisted of four treatments with three replications. The use of vitamin E doses was 0, 125, 250, and 375 mg/kg. The vitamin E was dissolved in vegetable oil and mixed with albumen as a binder in feed. The vitamin E was sprayed at feed and was air dried. Female broodstock of the fantail goldfishes were reared for 40 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…However, previous report showed the administration of vitamin E to fish feed in the amount of 300 mg kg -1 provides the best fecundity value compared to comet fish (James et al, 2008). Meanwhile, the administration of vitamin E at 375 mg kg -1 produced fecundity value of 56 eggs per gram compared to gold fish Carassius auratus (Arfah et al, 2013). In addition, the similar reports were also reported several researcher, for instance Izquierdo et al (2001), and Aryani and Hamdan (2014).…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…However, previous report showed the administration of vitamin E to fish feed in the amount of 300 mg kg -1 provides the best fecundity value compared to comet fish (James et al, 2008). Meanwhile, the administration of vitamin E at 375 mg kg -1 produced fecundity value of 56 eggs per gram compared to gold fish Carassius auratus (Arfah et al, 2013). In addition, the similar reports were also reported several researcher, for instance Izquierdo et al (2001), and Aryani and Hamdan (2014).…”
Section: Resultssupporting
confidence: 62%
“…This resulted to average values ranged between 18.5-21.43% and 25.45-27.88%, respectively, where the vitamin E acts as an antioxidant in an effort to prevent the oxidation of fatty acids during vitelogenesis. Research reported by the vitamin E potentially prevents fat oxidation during vitelogenin (Arfah et al, 2013). The fatty acid content was continuously allocated to the egg during gonad development later used as energy reserves for subsequent application.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultured sandfish broodstock needs longer time to mature and re-mature after spawning (Sembiring et al, 2017). Our proposed alternative to improve the reproduction performance of sandfish broodstock is by feeding them with vitamin E-supplemented feed which has shown to be effective for other freshwater fish and invertebrate species such as Mali fish (Labeobarbus festivus) need 150-450 mg/kg feed (Aryani et al, 2014), goldfish (Carassius auratus) need 375 mg/kg feed (Arfah et al, 2013), freshwater lobster, Astacus leptodactylus need 1,000 mg/kg feed (Barim-oz et al, 2011). Guppy fish, Poecilia reticulata need vitamin E 1,000 mg/kg feed for growth and good reproduction performance (Mehrad & Sudagar, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The addition of enriching ingredients in the form of glutathione and vitamin E is thought to be able to maintain the presence of fat granules, thereby increasing the number and size of egg yolk granules, resulting in an increase in egg volume and diameter [36]. As stated by [37], which stated that the addition of vitamin E to the feed can increase the size of the egg diameter of comet fish (Carassius auratus auratus). The egg must contain all the nutrients needed by the developing embryo and larva after the egg is fertilized so that the fish can meet their needs to initiate the consumption of external food.…”
Section: Discussionmentioning
confidence: 99%